Reforming suo tempore: Exploring the unintended consequences of the European Union's 'reform actorness'. (May 2023) - Blavoukos, Spyros; Oikonomou, Giorgio
The European Union is broadly considered a benign reform actor, encouraging and supporting reforms in member states and beyond. However, European Union-induced reforms do not only generate the intended effects; they can also trigger unintended consequences for other reforms. These unintended consequences occur primarily through the impact of European Union-induced reforms on the resources available. The scope and size of the unintended effects will be conditioned by the domestic cycles in economic and public policy-making. Here, we apply our analytical framework to study the resilience of governance reforms in Greece during the period of fiscal consolidation (2010–2015), highlighting the unintended consequences of the European Union's 'reform actorness'. We find that the distinction between financial and non-financial resources is critical in unpacking the unintended consequences of any exogenously driven reform. Depending on the current stage in the cycles, the impact on non-financial resources can generate positive side-effects that help prevent other ongoing domestic reforms being derailed.